Design guidelines for post-processing of laser beam melting in context of support structures - Künneke, Thomas; Lieneke, Tobias; Lammers, Stefan; Zimmer, Detmar (Proceedings of the Special Interest Group meeting on Advancing Precision in Additive Manufacturing)
Laser Beam Melting (LBM) is an Additive Manufacturing (AM) process on the threshold of serial production. Therefore, LBM has to overcome different problems such as a low productivity and minor economic efficiency. Support structures are essential for LBM; however, these structures contribute to the mentioned topics, because their removal is time consuming and cost intensive. To enable design engineers and operators to increase the efficiency of LBM, design guidelinesfor support structures suitable for post-processing are developed. For this purpose, the effect of different design parameters on various evaluation criteria is considered. Suitability for post-processing can be evaluated in terms of cost, quality and time. Therefore, test specimens are built and parameter impacts on material consumption as well as the post-processing time is examined. Furthermore, the roughness of the parts is analyzed and used as an indicator for the removability of the support structure. In addition, warpage is measured and the impact of the parameters on this criterion is examined. Based on the results, suitable design guidelines and hints for support structures are developed in order to reduce time and costs during manufacturing and post-processing.

Manufacturing Accuracy In Additive Manufacturing: A Method To Determine Geometrical Tolerances - Lieneke, Tobias; Künneke, Thomas; Schlenker, Fabian; Denzer, Vera; Zimmer, Detmar (Special Interest Group Meeting: Advancing Precision in Additive Manufacturing)
Additive Manufacturing (AM) processes generate plastic or metal parts layer-by-layer without using formative tools. The resulting advantages highlight the capability of AM to become an inherent part within the product development. However, process specific challenges such as a high surface roughness, the stair-stepping effect or geometrical deviations inhibit the industrial establishment. Thus, additively manufactured parts often need to be post-processed using established manufacturing processes. Many process parameters and geometrical factors influence the manufacturing accuracy in AM which can lead to large deviations and high scatterings. Published results concerning these deviations are also difficult to compare, because they are based on several geometries that are manufactured using different processes, materials and machine settings. It is emphasized that reliable tolerances for AM are difficult to define in standards. Within this investigation, a uniform method was developed regarding relevant test specimens to examine geometrical deviations for Laser Beam Melting (LBM), Fused Deposition Modeling (FDM) and Selective Laser Sintering (SLS) in order to derive geometrical tolerance values. The manufactured test specimens were measured using tactile and optical systems to examine the occurring geometrical deviations. The results show possible geometrical tolerance values that were classified according to the international standard DIN EN ISO 286-1.

Schall mittels Pulver dämpfen - Künneke, Thomas; Zimmer, Detmar (konstruktionspraxis)

Konzeption eines energieeffizienten Betätigungs- und Haltesystems für eine Federkraftbremse - Kriegel, Nils-Peter

The Common Enemy Effect under Strategic Network Formation and Disruption - Hoyer, Britta; Haller, Hans (Journal of Economic Behavior & Organization)
Social psychology studies the "common enemy effect", the phenomenon that members of a group work together when they face an opponent, although they otherwise have little in common. An interesting scenario is the formation of an information network where group members individually sponsor costly links. Suppose that ceteris paribus, an outsider appears who aims to disrupt the information flow within the network by deleting some of the links. The question is how the group responds to this common enemy. We address this question for the homogeneous connections model of strategic network formation, with two-way flow of information and without information decay. For sufficiently low linkage costs, the external threat can lead to a more connected network, a positive common enemy effect. For very high but not prohibitively high linkage costs, the equilibrium network can be minimally connected and efficient in the absence of the external threat whereas it is always empty and ineffi cient in the presence of the external threat, a negative common enemy effect. For intermediate linkage costs, both connected networks and the empty network are Nash for certain cost ranges.

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)

Enhancing the stability of DNA origami nanostructures: staple strand redesign versus enzymatic ligation - Ramakrishnan, Saminathan; Schärfen, Leonard; Hunold, Kristin; Fricke, Sebastian; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian; Krainer, Georg (Nanoscale)
Merging of bridging staples with adjacent oligonucleotide sequences leads to a moderate increase of DNA origami stability, while enzymatic ligation after assembly yields a reinforced nanostructure with superior stability at up to 37 °C and in the presence of 6 M urea.

Effect of Staple Age on DNA Origami Nanostructure Assembly and Stability - Kielar, Charlotte; Xin, Yang; Xu, Xiaodan; Zhu, Siqi; Gorin, Nelli; Grundmeier, Guido; Möser, Christin; Smith, David M.; Keller, Adrian (Molecules)
DNA origami nanostructures are widely employed in various areas of fundamental and applied research. Due to the tremendous success of the DNA origami technique in the academic field, considerable efforts currently aim at the translation of this technology from a laboratory setting to real-world applications, such as nanoelectronics, drug delivery, and biosensing. While many of these real-world applications rely on an intact DNA origami shape, they often also subject the DNA origami nanostructures to rather harsh and potentially damaging environmental and processing conditions. Furthermore, in the context of DNA origami mass production, the long-term storage of DNA origami nanostructures or their pre-assembled components also becomes an issue of high relevance, especially regarding the possible negative effects on DNA origami structural integrity. Thus, we investigated the effect of staple age on the self-assembly and stability of DNA origami nanostructures using atomic force microscopy. Different harsh processing conditions were simulated by applying different sample preparation protocols. Our results show that staple solutions may be stored at −20 °C for several years without impeding DNA origami self-assembly. Depending on DNA origami shape and superstructure, however, staple age may have negative effects on DNA origami stability under harsh treatment conditions. Mass spectrometry analysis of the aged staple mixtures revealed no signs of staple fragmentation. We, therefore, attribute the increased DNA origami sensitivity toward environmental conditions to an accumulation of damaged nucleobases, which undergo weaker base-pairing interactions and thus lead to reduced duplex stability.

Real-Time Observation of Superstructure-Dependent DNA Origami Digestion by DNase I Using High-Speed Atomic Force Microscopy. - Ramakrishnan, S; Shen, B; Kostiainen, MA; Grundmeier, Guido; Keller, Adrian; Linko, V (ChemBioChem)

DNA origami directed 3D nanoparticle superlattice via electrostatic assembly. - Julin, S; Korpi, A; Shen, B; Liljeström, V; Ikkala, O; Keller, Adrian; Linko, V; Kostiainen, MA (Nanoscale)

Effect of Terminal Modifications on the Adsorption and Assembly of hIAPP(20–29) - Hajiraissi, Roozbeh; Hanke, Marcel; Gonzalez Orive, Alejandro; Duderija, Belma; Hofmann, Ulrike; Zhang, Yixin; Grundmeier, Guido; Keller, Adrian (ACS Omega)

Dependance of Poly(acrylic acid) Interfacial Adhesion on the Nanostructure of Electrodeposited ZnO Films - Meinderink, Dennis; Orive, Alejandro Gonzalez; Ewertowski, Simon; Giner, Ignacio; Grundmeier, Guido (ACS Applied Nano Materials)

Spray coating of poly(acrylic acid)/ZnO tetrapod adhesion promoting nanocomposite films for polymer laminates - Meinderink, Dennis; Nolkemper, Karlo J.R.; Bürger, Julius; Orive, Alejandro G.; Lindner, Jörg K.N.; Grundmeier, Guido (Surface and Coatings Technology)

Strategische Planung des Wertschöpfungsbeitrags von HELLA für automatisiertes Fahren von morgen - Eckelt, Daniel; Bismark, Ronny; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Vorausschau und Technologieplanung)

Model Checking of Integratively Designed Product and Production Systems - Dumitrescu, Roman; Japs, Sergej; Kaiser, Lydia; Rasor, Rik (TdSE 2019)

Entwicklung einer Suchstrategie für ein medienbasiertes Technologiesanning am Beispiel der Antriebstechnik - Albers, Alexander; Ellermann, Kai Fabian; Kühn, Arno; Dumitrescu, Roman (15. Symposium für Vorausschau und Technologieplanung)

Einstieg in die Plattformökonomie - Drewel, Marvin; Gausemeier, Jürgen; Vaßholz, Mareen; Homburg, Nils (Symposium für Vorausschau und Technologieplanung)

Erfolg versprechende Industrie 4.0-Zielposition - Ermittlung unter Berücksichtigung zukünftiger Umfeldentwicklungen - Pierenkemper, Christoph; Reinhold, Jannik; Dumitrescu, Roman; Gausemeier, Jürgen (Industrie 4.0 Management)

Developing and Evaluating Concepts for a Digital Platform - Wortmann, Fabio; Joppen, Robert; Drewel, Marvin; Kühn, Arno; Dumitrescu, Roman (IAMOT 2019 – Proceedings of the 28th International Association for Management of Technology Conference, Apr. 2019 International Association for Management of Technology (IAMOT), IAMOT)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects)
Today's manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding value networks fundamentally differ from traditional ones. Developing smart services requires new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to adapt their value networks. However, the highly complex transformation of value crea-tion especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this paper, we introduce a basic framework for planning smart services and present a methodology for competence-based plan-ning of value networks for smart services in three phases: Smart service analysis, competence analysis and value creation planning. The methodology is explained by an example from tooling machine industry.